BIOAKTIVITAS EKSTRAKTIF LARUT ETANOL KULIT BAKAU (Rhizophora apiculata Blume) TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - yadi, Mul; Diba, Farah; Yani, Ahmad (JURNAL HUTAN LESTARI, 2014)
This research aimed to determine the effect of bioactivity and the optimum concentration of ethanol soluble extractives from bark of Rhizophora apiculata in control termites of Coptotermes curvignathus. In order to get a product new natural preservative in environmentally friendly. The experiment wasÂ  used a method of a forced feeding test from added extract of the bark of R. apiculata that consisting of 6 level concentration is 0% control, 2%, 4%, 6%, 8% and 10% by using Completely Randomized Design (CRD). The results showed that the concentration of 10% is the optimal concentration to inhibit the attack of subterranean termites that can deliver the highest mortality rate (100%) and the lowest weight loss of the paper test (35.21%). The results analysis of variety was showed that the extract of the paper test has a significant influence on mortality of termites C. curvignathus and has a significant effect on weight loss of the paper test. Extract Bark of R. apiculata with a concentration of 10% can be used as a potential natural preservative wood. Keywords: Bioactivity, ethanol, concentration, bark of mangrove, Coptotermes curvignathus